2012
DOI: 10.1038/labinvest.2012.49
|View full text |Cite
|
Sign up to set email alerts
|

Genetic background effects of keratin 8 and 18 in a DDC-induced hepatotoxicity and Mallory-Denk body formation mouse model

Abstract: Keratin 8 (K8) and keratin 18 (K18) form the major hepatocyte cytoskeleton. We investigated the impact of genetic loss of either K8 or K18 on liver homeostasis under toxic stress with the hypothesis that K8 and K18 exert different functions. krt8À/À and krt18 À/À mice crossed into the same 129-ola genetic background were treated by acute and chronic administration of 3,5-diethoxy-carbonyl-1,4-dihydrocollidine (DDC). In acutely DDC-intoxicated mice, macrovesicular steatosis was more pronounced in krt8 À/À and k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 46 publications
2
28
0
1
Order By: Relevance
“…Nevertheless, in the pediatric patients with NASH frequently deficiencies MDBs, which indicates that aging-related cumulative oxidative damages or genetic factors may take part a contributing effect (14,15). In addition, Haybaeck et al (16) demonstrated that the structural features of Keratin 8 and Keratin 18 are genetic agents that are independent of the influence of genetic background as toxicity effects rely on the genetic background in a DDC-stimulated hepatotoxicity and MDB occurrence mouse form. At present, the in situ proximity ligation assay (isPLA) is an increasingly utilized technology for the in situ determination of protein interactive relations, post-translational modifications, and spatial connections of antigens in cells and tissues, in general.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in the pediatric patients with NASH frequently deficiencies MDBs, which indicates that aging-related cumulative oxidative damages or genetic factors may take part a contributing effect (14,15). In addition, Haybaeck et al (16) demonstrated that the structural features of Keratin 8 and Keratin 18 are genetic agents that are independent of the influence of genetic background as toxicity effects rely on the genetic background in a DDC-stimulated hepatotoxicity and MDB occurrence mouse form. At present, the in situ proximity ligation assay (isPLA) is an increasingly utilized technology for the in situ determination of protein interactive relations, post-translational modifications, and spatial connections of antigens in cells and tissues, in general.…”
Section: Discussionmentioning
confidence: 99%
“…This does not seem to be due to differences in porphyrin accumulation given that similar levels were found in both groups. The latter observation is not surprising since K8-loss also did not result in porphyrin retention [167]. A reduced bile flow might be responsible for the increased stone formation, given that DDC feeding leads to reduced bile flow in both K8-and K18-KO mice compared to DDC-fed WTs [126].…”
Section: K19-ko Mice Suffer a More Severe Ddc-induced Biliary Injurymentioning
confidence: 81%
“…Collectively, the combination of the above clinical findings suggests that loss of K19 leads to a more severe DDC-induced cholestatic liver injury. In contrast, loss of either K8 or K18 had no effect on the DDC-induced cholestasis since comparable levels of serum ALP and total bilirubin were measured both 1 week and 12 weeks after DDC feeding [167]. On the other hand, the peak of DDC-induced biliary injury occurs 4 weeks after the start of feeding, and this time point might therefore be more useful to evaluate the role of K8/K18 in DDC-induced biliary injury.…”
Section: K19-ko Mice Suffer a More Severe Ddc-induced Biliary Injurymentioning
confidence: 96%
See 2 more Smart Citations